2022
DOI: 10.3389/fpsyt.2022.923076
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Resting Cerebral Blood Flow, Neurometabolites, Cardio-Respiratory Fitness and Aging-Related Cognitive Decline

Abstract: Older adults typically experience a decline in cognitive function, but improvements in physical health and lifestyle can be neuroprotective across the human lifespan. The primary objective of this study is to advance our basic understanding of how cardiorespiratory fitness and neurophysiological attributes relate to cognitive decline. While cerebral blood flow (CBF) is critical for the supply of nutrients to the tissue, the brain’s major neurotransmitters (i.e., gamma-aminobutyric acid, GABA, and glutamate-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…17,19,27,86 However, the present data found no association between cardiorespiratory fitness and global or regional CBF. Other cross-sectional ASL studies report no global effect, 33,52,54 but positive regional associations are generally observed. 33,3639 Previously reported regional effects often relate to much smaller regions than those examined in the present study (e.g., occipitoparietal area, posterior cingulate cortex, precuneus, middle frontal gyrus), and CBF was not adjusted for ATT differences in those studies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…17,19,27,86 However, the present data found no association between cardiorespiratory fitness and global or regional CBF. Other cross-sectional ASL studies report no global effect, 33,52,54 but positive regional associations are generally observed. 33,3639 Previously reported regional effects often relate to much smaller regions than those examined in the present study (e.g., occipitoparietal area, posterior cingulate cortex, precuneus, middle frontal gyrus), and CBF was not adjusted for ATT differences in those studies.…”
Section: Discussionmentioning
confidence: 78%
“…40 Furthermore, aerobic exercise training in older adults has been shown to increase CBF 28,[41][42][43][44][45] or CBv. [46][47][48][49] In contrast, a negative association between cardiorespiratory fitness and CBF has also been found 50,51 or a complete lack of association between cardiorespiratory fitness and CBF [52][53][54] or CBv. [55][56][57][58][59] Interestingly, reported changes in CBF are not usually global, but instead confined to specific regions of the brain.…”
Section: Introductionmentioning
confidence: 98%
“…Such a result, though counterintuitive, is not beyond the realm of possibility. A theoretical, yet empirically elusive, construct in the stroke literature is the concept of diaschisis ( Carrera and Tononi, 2014 )—defined as “neurophysiological changes that occur distant to a focal brain lesion.” It may be that loss of input and output to a region distal to the lesion may cause an increase in blood flow due to a reduction in inhibitory tone ( Blicher et al, 2015 ), which together (i.e., GABA and CBF) influence cognitive decline ( Krishnamurthy V. et al, 2022 ; Krishnamurthy L. C. et al, 2022 ). Therefore, an increased CBF distal to the lesion may indicate a failure of the network and lead to worse behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, multi-modal neuroimaging approaches that combine magnetic resonance spectroscopy (MRS) and functional magnetic resonance imaging (fMRI) are highly informative in such endeavors (for a descriptive review see ( 5 ) and a comprehensive meta-analysis see ( 6 )), but all reports to date examine younger or midlife populations. While we recently showed that the flow-metabolism coupling (i.e., associations between neurometabolites and cerebral blood flow) is critical in aging-related cognitive decline ( 7 ), the role of neurometabolites in task engagement is yet to be explored in an aging model, Furthermore, most reports relate MRS measures with task-BOLD amplitude, but the shape of the hemodynamic response is also of great importance when relating to neurochemistry ( 8 ), especially in an aging model.…”
Section: Introductionmentioning
confidence: 99%
“…
and Krishnamurthy V (2022) The association between language-based task-functional magnetic resonance imaging hemodynamics and baseline GABA+ and glutamate-glutamine measured in pre-supplementary motor area: A pilot study in an aging model.
…”
mentioning
confidence: 99%